DEVELOPING THE PROBLEM OF NUMERATION LITERACY WITH ISLAMIC CONTEXT - Setyawati, Maunah; Aisyah, Habsanul; Kusaeri, Kusaeri (MaPan : Jurnal Matematika dan Pembelajaran, 2021)
This study aims to develop assessment questions or instruments to measure students' numeration literacy skills integrated with the Islamic context. The research was conducted through 4 stages: initial assessment, design, test making, and a study of problem items then limited trials and analysis. The instruments used include algebra and statistics by taking the Islamic context of zakat material. Experts validated the instrument, and the validation results were analyzed using Aiken's formula. The instrument was also tested online and limited to 22 students of grade 8 MTsN 1 Surabaya. The test results were analyzed using product-moment correlation to determine its empirical validity and used alpha Cronbach to determine its reliability. The results showed that the 6 questions developed are valid with a validity value of 0.783. This result is reinforced by empirical validity results that show that the instruments developed are valid in terms of material/content, construct, and language. The reliability test results using alpha Cronbach obtained the reliability coefficient is 0.72. The instrument developed in this research is expected to be one of the references of students in practicing their numeracy skills and preparing to face national assessments by the Ministry of Education. Because it was found in this study that students have difficulty answering the question of numeration literacy with Islamic context. This case shows that students' numeration literacy skills are still low.